How does monetary policy affect the income class structure? Evidence from the Eurozone. - Martín-Fuentes, Natalia; Pérez-Moreno, Salvador Jesús; Bárcena-Martín, Elena María (My University, 2019)
This work provides evidence on the potential effects of monetary policy on the income class structure via stimulating economic activity and employment in the Eurozone countries over the period 2007Q3-2016Q1. Based on European Union Statistics on Income and Living Conditions (EU-SILC) data, we compute the size of income classes (lower, lower-middle, upper-middle, and upper) for the stats that originated the Economic and Monetary Union (EMU-11) and analyse the impact of monetary policy impulses under a Bayesian Vector Autoregressive approach. We focus on the earnings heterogeneity and the income composition channel and find that a monetary easing shock involving a decrease short-term nominal interest rate has diverse effects on the different income classes, which seems to have led to a more equal income distribution. As theoretically argued by these monetary policy transmission mechanisms, our results confirm the GDP growth and the decrease in unemployment caused by the monetary policies implemented by the European Central Bank since the onset of the financial crisis have had a positive effect for those households located at the bottom of the income-class structure as well as for the middle class.
Keywords: Política monetaria - Paises de la Unión Europea - 21; Desigualdad social - Paises de la Unión Europea; Eurozona; Política monetaria; Clase media; Desigualdad de renta; Estructura de clases; Bayesian VAR